Implementation and Impact of a Maternal–Fetal Medicine Telemedicine Program - Leighton, Cassandra; Conroy, Molly; Bilderback, Andrew; Kalocay, Wendy; Henderson, James K.; Simhan, Hyagriv N. (American Journal of Perinatology, 2019)
Objective The increase in maternal morbidity has resulted in higher need for maternal–fetal medicine (MFM) subspecialty care. To meet the rising demand, particularly in rural areas, the use of MFM telemedicine services has increased. This study describes the structure, implementation, and patient and child health outcomes associated with a large health system's MFM telemedicine program.Study Design Observational electronic health record data are used to compare maternal and childbirth outcomes between patients receiving care via telemedicine or in-person visits through regression analysis. Average patient time and resources saved are calculated, and patient satisfaction scores are reported.Results The telemedicine patients experienced similar outcomes to the in-person group, indicating that MFM telemedicine can serve as an effective substitute for in-person care. MFM telemedicine patients saved $90.28 per consult in travel and work-related expenses. An overwhelming majority of MFM telemedicine patients were satisfied with their visit and indicated that they would be interested in receiving care via telemedicine in the future.Conclusion The results indicate that the patients may benefit financially and experience similar outcomes when telemedicine programs are appropriately designed to eliminate access barriers and provide high-quality care.
Keywords: maternal–fetal medicine; telemedicine; maternal; child; teleconsult